Overview of Community Knowledge and Attitudes in Efforts to Prevent Pulmonary Tuberculosis: Literature Review - Landudjama, Leni; Noviana, Ineke (Poltekkes Kemenkes Kupang, 2024)
Pulmonary tuberculosis (TB) remains a significant public health problem globally and nationally, including in Indonesia. The success of TB control is greatly influenced by public knowledge and attitudes towards the disease. However, knowledge gaps, negative attitudes, and stigma remain, hindering TB prevention and treatment. This study aims to examine the public's knowledge and attitudes regarding pulmonary tuberculosis prevention through a literature review of studies published between 2021 and 2023. This study used a short systematic literature review method with a focus on cross-sectional observational studies that measured knowledge, attitudes, and practices (KAP) towards TB in various populations. A literature search was conducted on Google Scholar, PubMed, and other repositories with relevant articles from 2021-2023 as inclusion criteria. Of the 9 articles that met the inclusion criteria, it was found that the level of public knowledge about TB varied between 44% and 75%, while positive attitudes ranged from 11% to 91%. Factors influencing knowledge and positive attitudes were education level, socioeconomic status, residence, and access to health information. Although the majority of people have good knowledge and attitudes, obstacles such as social stigma and misconceptions still hinder effective preventive behavior. Public knowledge and attitudes toward pulmonary TB vary and are strongly influenced by socioeconomic and educational factors. Community-based health education and communication campaigns tailored to local cultures are crucial to raise awareness, reduce stigma, and support TB prevention.